The newcomer [large type] - Fisher, Suzanne Woods (Fisher, Suzanne Woods. Amish beginnings novel, 2017)
In 1737, Anna Konig and her fellow church members stagger off a small wooden ship after ten weeks at sea, eager to start a new life in the vibrant but raw Pennsylvania frontier. On the docks of Port Philadelphia waits bishop Jacob Bauer, founder of the settlement and father to ship carpenter Bairn. It's a time of new beginnings for the reunited Bauer family, and for Anna and Bairn's shipboard romance to blossom. But this perfect moment cannot last. As Bairn grasps the reality of what it means to be Amish in the New World -- isolated, rigid with expectations, under the thumb of his domineering father -- his enthusiasm evaporates. When a sea captain offers the chance to cross the ocean one more time, Bairn grabs it. Just one more crossing, he promises Anna. But will she wait for him? When Henrik Newman joins the church just as it makes its way to the frontier, Anna is torn. He seems to be everything Bairn is not -- bold, devoted, and delighted to vie for her heart. And the most dramatic difference? He is here; Bairn is not. Far from the frontier, an unexpected turn of events weaves together the lives of Bairn, Anna, and Henrik. When a secret is revealed, which true love will emerge?